Knowledge, attitude and practices regarding vitamin D among adults in Ghana: a cross-sectional study - Abraham Ameyaw Kwabena; Benedicta Appiah; Samuel Ankomah Danso; Samuel Kwame Sopuruchi Agomuo; Samuel Kwarteng; Ebenezer Senu; Alfred Effah; Samuel Asamoah Sakyi; Linda Ahenkorah Fondjo (BMC Public Health, 2025)
Abstract Background Vitamin D deficiency is a major public health concern, affecting approximately half of the world's population, partly due to limited public knowledge about vitamin D sources. However, there is lack of data on awareness, knowledge, attitudes, and practices regarding vitamin D in high-risk countries like Ghana. We investigated vitamin D awareness, knowledge and its associated factors in the Ghanaian population. Methods This cross-sectional study involved 515 adults from Jaman South Municipal between January and June 2024. Questionnaires were used to obtain data on demographics, clinical characteristics, awareness and knowledge, attitude and practices towards vitamin D. Binary logistic regression analysis was used to determine the independent predictors of knowledge and practices regarding vitamin D. SPSS (version 26.0) was used for all statistical analysis. P < 0.05 was considered statistically significant. Results Awareness, knowledge, attitude and practice level towards vitamin D was 61%, 56.9%, 63.7% and 73.2% respectively. Aged between 18–24 yrs [(aOR = 4.106, 95% CI: (1.523–11.072); p = 0.005)], being single [(aOR = 0.243, 95% CI: (0.065–0.904); p = 0.035)], having basic [(aOR = 0.216, 95% CI: (0.068–0.685); p = 0.009)] or secondary education [(aOR = 0.151, 95% CI: (0.073–0.313); p < 0.001)] and speaking English [(aOR = 3.553, 95% CI: (1.519–8.313); p = 0.003)] were the independent predictors of adequate knowledge on vitamin D. Having basic [(aOR = 9.058, 95% CI: (2.449–33.509); p = 0.001)] or secondary education [(aOR = 5.252, 95% CI: (2.508–10.996); p < 0.001)] increased the likelihood of good practices. Conclusion There is high awareness but reduced knowledge on Vitamin D among the general public in Jaman South. Age, education, employment status, language were the factors associated with knowledge and practice regarding vitamin D. There is need for extensive health educational campaigns to the public to boost the knowledge levels on the importance of Vitamin D.